2010
DOI: 10.1021/jo101596d
|View full text |Cite
|
Sign up to set email alerts
|

Rh-Catalyzed Oxidative Coupling between Primary and Secondary Benzamides and Alkynes: Synthesis of Polycyclic Amides

Abstract: A methodology for the high yield and facile synthesis of isoquinolones from benzamides and alkynes via the oxidative ortho C-H activation of benzamides has been developed. Ag(2)CO(3) proved to be an optimal oxidant when MeCN was used as a solvent, and [RhCp*Cl(2)](2) was utilized as an efficient catalyst. Both N-alkyl and N-aryl secondary benzamides can be applied as effective substrates. Furthermore, primary benzamides react with two alkyne units, leading to tricyclic products via double C-H activation and ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
92
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 308 publications
(99 citation statements)
references
References 42 publications
4
92
0
3
Order By: Relevance
“…(1)], [6] thus resulting in the generation of undesired waste. Recently, Fagnou et al reported an oxidizing-directing-group strategy [7] for the rhodium-catalyzed synthesis of isoquinolones by intermolecular CÀH activation of N-methoxy/pivaloyloxy benzamides and alkynes [Eq.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(1)], [6] thus resulting in the generation of undesired waste. Recently, Fagnou et al reported an oxidizing-directing-group strategy [7] for the rhodium-catalyzed synthesis of isoquinolones by intermolecular CÀH activation of N-methoxy/pivaloyloxy benzamides and alkynes [Eq.…”
mentioning
confidence: 99%
“…The indolizidine structural motif forms the core of many natural products with pharmacological relevance, such as indolizidine [1] and phenanthroindolizidine [2] alkaloids (septicine (1), antofine (2), and tylophorine (3)), camptothecin (4, CPT), [3] and aromathecin alkaloids [4] (rosettacin (5) and 22-hydroxyacuminatine (6)). While a number of synthetic methods for the construction of these scaffolds have been reported, [1][2][3][4] the development of conceptually different synthetic approaches is still of great interest.…”
mentioning
confidence: 99%
“…4 The proposed mechanism for the Co(III)-catalyzed coupling of alkynes and amides to afford isoquinolones is closely related to the analogous Rh(III)-catalyzed reaction (Fig. 2) [55][56][57][58]. Coordination of the amide and quinoline moieties generates intermediate 8 that can undergo C-H activation, presumably via a CMD mechanism to generate metallacycle 9.…”
Section: Cobalt Catalysismentioning
confidence: 98%
“…(5.57) and (5.58)). Both N-alkyl and N-aryl secondary benzamides could be employed, whereas primary benzamides reacted differently, and two alkyne units were oxidatively incorporated to give tricyclic products such as 60 [33]. The reaction was further extended to the annulation of N-pivaloxybenzamide with terminal alkynes to give 3-substituted isoquinolones 61 with good regioselectivity under mild conditions (Eq.…”
Section: Synthesis Of Isoquinolones and Related Derivativesmentioning
confidence: 99%